Marketing Aspect Analysis of Shrimp Farm Sales in the Coastal Area of Kwanyar Village - Moh. Danial Ismail; Abdur Rahman (Demagogi: Journal of Social Sciences, Economics and Education, 2025)
Kwanyar Village, located in the coastal area of ​​Bangkalan Regency, East Java, has great potential in developing shrimp farming. However, the success of production has not been matched by an optimal marketing system. This study aims to analyze the marketing aspects in the sale of shrimp farm products in the village, including distribution channels, promotional strategies, market barriers, and development opportunities. The research method uses a qualitative descriptive approach through interviews, field observations, and literature reviews. The results of the study show that product distribution still depends on collectors, promotional strategies are not optimal, and market information is very limited. Recommendations include strengthening the capacity of shrimp farmers in marketing strategies, digitalization of distribution channels, and support for local policies.